1997
DOI: 10.1093/infdis/175.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Wuchereria bancrofti Adult Worm Circulating Antigen after Annual Treatments of Diethylcarbamazine Combined with Ivermectin in French Polynesia

Abstract: Circulating filarial antigen (CFA), determined with Og4C3 ELISA, is a marker of Wuchereria bancrofti adult worm infection. The reduction of CFA over 2 years was determined in 185 microfilaremic and 111 amicrofilaremic but CFA+ adults given an annual dose of either diethylcarbamazine (DEC) or ivermectin or the two combined. Reduction of CFA level was good with DEC but weak with ivermectin and followed the same pattern in amicrofilaremic and microfilaremic groups. Combinations and DEC alone had a similar impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…Our results contradict these observations and clearly show that there is a significant association (p = 0.001) between the density of MF and the concentration of CFA. Similar results were obtained by Rocha et al (1996), Nicolas et al (1997) and Itoh et al (1999). We also agree with Grove and Davis (1978), who suggest that the detection of microfilarial antibodies depends upon the relative release of MF into the bloodstream and the production of antibodies against those MF.…”
Section: Discussionsupporting
confidence: 92%
“…Our results contradict these observations and clearly show that there is a significant association (p = 0.001) between the density of MF and the concentration of CFA. Similar results were obtained by Rocha et al (1996), Nicolas et al (1997) and Itoh et al (1999). We also agree with Grove and Davis (1978), who suggest that the detection of microfilarial antibodies depends upon the relative release of MF into the bloodstream and the production of antibodies against those MF.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies (including this article), do not agree with this hypothesis (Rocha et al 1996, Nicolas et al 1997, Itoh et al 1999). These authors demonstrated on the contrary that the CFA intensity is directly proportional to the microfilaremia density, i.e., the higher the MF density, the higher the CFA levels.…”
Section: Study Population and Parasitological Profile -mentioning
confidence: 69%
“…Such quantitative assays have now been used not only for cross-sectional 15,16 and longitudinal 17 analyses of community prevalence, but also for surveying populations in lymphatic filariasis-endemic regions after treatment. [18][19][20] As the use of antifilarial drugs becomes more widespread in many endemic regions, the opportunities for studying drug-naive populations using these newer, more refined antigen detection techniques become fewer and fewer. Therefore, in the present study, we have taken advantage of the opportunity to reexamine a population residing on an island in the South Pacific, which had been studied before the introduction of antifilarial chemotherapy.…”
Section: Introductionmentioning
confidence: 99%